Traum'cast: an online, open-access educational video podcast series for teaching military trauma care to all healthcare providers. (10th March 2021) - Boutonnet, Mathieu; Benbrika, Widad; Facione, Julia; Travers, Stéphane; Boddaert, Guillaume; Colas, Marie-Dominique; Hornez, Emmanuel; Mathieu, Laurent; de Régloix, Stanislas; Daban, Jean-Louis; Leclerc, Thomas; Pasquier, Pierre; et al.
Abstract : The aim of this paper was to describe the development of 'Traum'cast', an ambitious project to create a high-quality, open-access, 12-week video podcast programme providing evidence-based continuing medical education for civilian and military healthcare practitioners dedicated to the management of trauma caused by weapons of war. The management of such patients became a particular public health issue in France following the 2015 terrorist attacks in Paris, which highlighted the need for all healthcare professionals to have appropriate knowledge and training in such situations. In 2016, the French Health General Direction asked the French Military Medical Service (FMMS) to create a task force and to use its unique and considerable experience to produce high-quality educational material on key themes including war injuries, combat casualty care, triage, damage control surgery, transfusion strategies, psychological injury and rehabilitation. The material was produced by FMMS and first broadcast in French and for free, on the official FMMS YouTube channel in September 2020. Traum'cast provides evidence-based continuing medical education for civilian and military healthcare practitioners. Traum'cast is an educational innovation that meets a public health requirement.